Inside OrCAD - Schroeder, Chris, 1954- (EDN series for design engineers)
Inside OrCAD goes beyond the reference guide supplied by OrCAD. It contains an overview and introduction to modern schematic drafting, with exercises intended to help the reader master the use of OrCAD via a 'hands-on' learning experience - information that has been de-emphasized in the manuals for recent OrCAD versions. This introduction to OrCAD is designed to give easy access to practical information. The command reference is a complete listing and explanation of the OrCAD commands and functions. A series of appendices provide important tips and techniques and information about linking OrCAD to other Computer Aided Design and Computer Aided Engineering tools used in the electronics design process. The enclosed disk contains a parts library for the tutorial exercises and several useful utilities, making this book a valuable tool for the design engineer or engineering student. Chris Schroeder is the Technical Director, Electronics, For Crane Technologies Group, Inc., Daytona Beach, Florida, a leading automotive aftermarket and original equipment supplier. He has 19 years of engineering, marketing, and management experience in the electronics industry and has a broad, yet in-depth technical knowledge of both design and manufacturing. His specialized areas of design expertise include: embedded controls using RISC microcontroller technology, assembly language programming, magnetic design for switching power supplies and ignition coils, and printed circuit board design, including the use of surface mount technology. Provides a detailed tutorial. Contains tips and techniques for design engineers. Includes a library and utilities disc.